PENGGUNAAN E-MODUL BERBASIS KEARIFAN LOKAL PANTURA DALAM MENINGKATKAN KECERDASAN LOGIS PADA SISWA AUTIS - Izzah, Nurul; Ardiyanti, Sekar Dwi; Khamdun, Khamdun (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study analyzes the effectiveness of interactive e-modules based on Pantura local wisdom in teaching animal and plant body parts to autistic students in a fourth-grade class at SDLB Sunan Kudus. Employing a qualitative descriptive approach, the research utilized structured interviews with the class teacher and direct observations of classroom activities to gather data on the implementation of the e-modules and their impact on student engagement and learning outcomes. Findings reveal that these locally grounded e-modules significantly enhance the logical intelligence and problem-solving skills of autistic students by facilitating a more engaging learning experience that connects educational content with their local environment, thereby increasing motivation and participation in science education. The study highlights the necessity of using concrete and visual learning materials, as autistic students benefit from tangible resources that aid comprehension. Additionally, the integration of technology, such as voice recorders and interactive media, supports the learning process by making it more accessible and enjoyable. The results emphasize the critical role of culturally relevant teaching methods and the need for ongoing guidance and supervision to foster the academic and cognitive growth of students with special needs, contributing to the understanding of effective pedagogical strategies in special education and advocating for the incorporation of local wisdom and technological tools to enhance learning outcomes for autistic students.